"The Master of the House"—Agencies in Municipal Service Provision: Balancing Autonomy and Accountability. (May 2017) - Andersen, Ole Johan; Torsteinsen, Harald
The article raises the question of to what extent municipalities adopting reforms of decentralization are able to find a stable balance between strategic management and operational autonomy. We performed a case study in a Norwegian municipality with more than 10 years of experience in practicing the agency model characterized by a radical disaggregation and autonomization of functions. Our findings suggest that finding a stable balance seems hard to obtain. Instead, there is a continuous process of "negotiation" going on between the two levels. The risk of sliding back to hierarchy and central rule seems to be more or less permanent.